Botulinum Toxin Treatment What Everyone Should Know - Jabbari, Bahman (Springer International Publishing, 2018)
Several books have been written on the subject of botulinum toxin and other neurotoxins for treatment of medical disorders including two Springer publications by Dr. Jabbari. However, despite the huge interest and enthusiasm of the public to learn more about this and other toxins, there is currently no book in the market on this subject which is specifically designed to inform and educate the public on botulinum toxin therapy. Botulinum Toxin Treatment explains and discusses in simple language the structure and function of botulinum toxin and other neurotoxins as well as the rational for its utility in different disease conditions. Safety, factors affecting efficacy, and duration of action, as well as cost and insurance issues are also addressed.